2017
DOI: 10.1080/21645515.2017.1296994
|View full text |Cite
|
Sign up to set email alerts
|

Receptor-binding domain of MERS-CoV with optimal immunogen dosage and immunization interval protects human transgenic mice from MERS-CoV infection

Abstract: Middle East respiratory syndrome (MERS) continues to raise worldwide concerns due to its pandemic potential. Increased MERS cases and no licensed MERS vaccines highlight the need to develop safe and effective vaccines against MERS. We have previously demonstrated that a receptor-binding domain (RBD) fragment containing residues 377-588 of MERS-coronavirus (MERS-CoV) spike protein is a critical neutralizing domain and an important vaccine target. Nevertheless, its optimal immunogen dosage and immunization inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(58 citation statements)
references
References 54 publications
0
57
0
1
Order By: Relevance
“…It is also widely used in vaccine development. Wang et al [30] reported that MERS-CoV S1 protein formulated with MF59 adjuvant protected hDPP4 transgenic mice against lethal virus challenge, and the protection correlated well with the neutralizing antibody titer. Adney et al [31] confirmed that immunization with adjuvanted S1 protein reduced and delayed virus shedding in the upper respiratory tract of dromedary camels and complete protection was observed in alpaca against MERS-CoV challenge.…”
Section: S1 Subunitmentioning
confidence: 99%
“…It is also widely used in vaccine development. Wang et al [30] reported that MERS-CoV S1 protein formulated with MF59 adjuvant protected hDPP4 transgenic mice against lethal virus challenge, and the protection correlated well with the neutralizing antibody titer. Adney et al [31] confirmed that immunization with adjuvanted S1 protein reduced and delayed virus shedding in the upper respiratory tract of dromedary camels and complete protection was observed in alpaca against MERS-CoV challenge.…”
Section: S1 Subunitmentioning
confidence: 99%
“…For SARS-CoV and MERS-CoV, these are mostly developed from spike glycoprotein S, RBD or nucleocapsid protein. [212][213][214][215][216] Some studies show that subunit vaccines given intranasally might induce stronger immune responses and mucosal immunity. 217 Several subunit vaccines have shown to be successful in animal challenging studies.…”
Section: Subunit and Recombinant Vaccinesmentioning
confidence: 99%
“…This is likely related to a traditional phenomenon, namely self-limitation or resolution, in which the neutralizing antibodies titer is decreased following the booster immunization as a response to the administrated antigens [24,25]. Several studies showed that the protective efficacy of MERS-CoV vaccines positively correlates with the evoked neutralizing antibody titers in the serum of vaccinated animals [26,27]. These results are in accordance with the results of other viral platforms chimeric viruses carrying spike protein which provided nAbs against MERS-CoV [9,28].…”
Section: Discussionmentioning
confidence: 99%